Negative active material, negative electrode, and battery

CN122996510APending Publication Date: 2026-10-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580023555.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-03-26
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0017]根据本公开的技术,对于使用了含有硅的材料的负极活性物质,能够减少负极因充电导致的膨胀。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996510A_ABST
    Figure CN122996510A_ABST
Patent Text Reader

Abstract

The negative electrode active material (10) of the present disclosure includes: a silicon-containing particle (11); a water-insoluble resin (12) attached to at least a portion of a surface of the silicon-containing particle (11); and a low-hardness material (13) attached to the surface of the silicon-containing particle (11) by the resin (12). The low-hardness material (13) is at least one selected from the group consisting of a mineral having a Mohs hardness of 1 and an inorganic compound having a Mohs hardness of 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to negative electrode active materials, negative electrodes, and batteries. Background Technology

[0002] In recent years, secondary batteries, represented by lithium-ion batteries, have been widely used as power sources for portable electronic devices and electric vehicles. Meanwhile, the utilization of silicon (Si) materials, as a high-theoretical-capacity negative electrode active material, has attracted considerable attention.

[0003] However, the volume of silicon-containing anode active materials increases significantly during charging, causing the anode containing silicon-containing anode active materials to expand during charging. Previously, techniques for suppressing electrode expansion caused by repeated charge-discharge cycles have been proposed. For example, Patent Document 1 discloses a composition comprising a specific block copolymer acting as a binder, non-conductive inorganic particles, a solvent, and electrode active material particles, as a composition for a non-aqueous secondary battery functional layer capable of forming an electrode binder layer. The electrode binder layer formed by this composition can suppress the expansion of the secondary battery due to repeated charge-discharge cycles and also improve the charge carrier acceptance of the secondary battery at low temperatures.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Publication No. 2019 / 194194 Summary of the Invention

[0007] The problem the invention aims to solve

[0008] However, as mentioned above, the volume of silicon-containing anode active materials increases significantly during charging. Therefore, in conventional technologies, there is room for improvement in effectively reducing anode expansion when using silicon-containing materials as anode active materials.

[0009] This disclosure provides a technique for reducing the expansion of the negative electrode due to charging in a negative electrode active material that uses silicon-containing materials.

[0010] Solution for solving the problem

[0011] The negative electrode active material disclosed herein possesses:

[0012] Silicon-containing particles;

[0013] At least a portion of the water-insoluble resin adhering to the surface of the silicon-containing particles; and

[0014] The low-hardness material adheres to the surface of the silicon-containing particles using the resin.

[0015] The low-hardness material is at least one selected from the group consisting of minerals with a Mohs hardness of 1 and inorganic compounds with a Mohs hardness of 1.

[0016] The effects of the invention

[0017] According to the technology disclosed herein, for negative electrode active materials using silicon-containing materials, it is possible to reduce the expansion of the negative electrode due to charging. Attached Figure Description

[0018] Figure 1 This is a schematic cross-sectional view illustrating a simplified configuration of an example of the negative electrode active material in Embodiment 1.

[0019] Figure 2 This is a schematic cross-sectional view illustrating a simplified configuration of a modified example of the negative electrode active material of Embodiment 1.

[0020] Figure 3 This is a simplified cross-sectional view showing an example of the structure of silicon-containing particles as particles of a composite material containing Si.

[0021] Figure 4 This is a cross-sectional view showing a simplified configuration of an example of the negative electrode in Embodiment 2.

[0022] Figure 5 This is a longitudinal sectional view schematically illustrating an example of the battery in Embodiment 3. Detailed Implementation

[0023] [Insights that form the basis of this disclosure]

[0024] In order to reduce the expansion of the negative electrode during charging, the inventors studied the structure of the expanding negative electrode using silicon-containing materials. Based on this study, it was confirmed that the porosity of the expanded negative electrode increased compared to the negative electrode before expansion. That is, the inventors found that the pores present in the negative electrode before expansion, i.e., before charging, were not effectively used as space to absorb the expansion of the negative electrode active material, thereby causing it to expand larger during charging.

[0025] Therefore, the inventors conducted further in-depth research and discovered that by imparting slip properties to the surface of the silicon-containing material, allowing the silicon-containing material to slide during expansion, the pores present before expansion can be effectively used as space to absorb the expansion of the negative electrode active material. Consequently, the inventors conceived of the negative electrode active material of this disclosure, as described below, which can reduce the expansion of the negative electrode.

[0026] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. The present disclosure is not limited to the following embodiments.

[0027] [Implementation of this disclosure]

[0028] (Implementation Method 1)

[0029] Figure 1 This is a schematic cross-sectional view illustrating a simplified configuration of an example of the negative electrode active material of Embodiment 1. The negative electrode active material 10 of Embodiment 1 comprises: silicon-containing particles 11; a resin 12 adhering to at least a portion of the surface of the silicon-containing particles; and a low-hardness material 13 adhering to the surface of the silicon-containing particles 11 by means of the resin 12. The resin 12 is a water-insoluble resin. The low-hardness material 13 is at least one selected from the group consisting of minerals with a Mohs hardness of 1 and inorganic compounds with a Mohs hardness of 1.

[0030] In this specification, water-insoluble resin refers to a resin whose solubility in water at room temperature (e.g., 25°C) is less than 0.1 g / L. For example, when an object containing resin is stirred in water at room temperature and the supernatant is analyzed, if the resin content in the water is less than 0.1 g / L, the resin is considered to be water-insoluble.

[0031] The negative electrode active material 10 includes a low-hardness material 13 attached to the surface of the silicon-containing particles 11. According to this configuration, the low-hardness material 13 imparts sliding properties to the surface of the silicon-containing particles 11. Therefore, even if the negative electrode active material 10 expands due to the increase in volume of the silicon-containing particles 11 during charging, the negative electrode active material 10 can slide and move, for example, into the pores that existed within the negative electrode before the expansion. Thus, it is considered that the negative electrode active material 10 can effectively use the pores existing before expansion as spaces to absorb the expansion of the negative electrode active material 10. Therefore, the negative electrode active material 10 can suppress a significant increase in the thickness of the negative electrode due to the expansion of the negative electrode active material 10 during charging; that is, it can reduce the expansion of the negative electrode caused by charging.

[0032] Furthermore, the low-hardness material 13 is firmly attached to the surface of the silicon-containing particles 11 by the resin 12, so the low-hardness material 13 is not easily detached from the surface of the silicon-containing particles 11. Therefore, even when the negative electrode active material 10 is mixed with other materials during the preparation of the negative electrode mixture, the aforementioned effects brought about by the low-hardness material 13 can still be obtained because the low-hardness material 13 is loaded on the surface of the silicon-containing particles 11.

[0033] A low-hardness material 13 is preferably located on the outermost surface of the negative electrode active material 10. According to this configuration, the surface slippage of the negative electrode active material 10 is improved, thus making it easier for the negative electrode active material 10 to move within the negative electrode. Therefore, the negative electrode active material 10 can reduce the expansion of the negative electrode due to charging.

[0034] As a variation of the negative electrode active material 10, the silicon-containing particles 11 may have a conductive layer on at least a portion of their surface. Figure 2This is a simplified cross-sectional view schematically illustrating a modified example of the negative electrode active material of Embodiment 1. (e.g.) Figure 2 As shown, in the modified negative electrode active material 20, in the configuration of the negative electrode active material 10, at least a portion of the surface of the silicon-containing particles 11 has a conductive layer 11a. In other words, in the negative electrode active material 20, the silicon-containing particles 11 are formed from a master particle 11b formed of a silicon-containing material and a conductive layer 11a covering at least a portion of the surface of the master particle 11b. According to this configuration, the conductivity of the silicon-containing particles 11 is improved. In the negative electrode active material 20, resin 12 is, for example, attached to the conductive layer 11a of the silicon-containing particles 11.

[0035] like Figure 2 As shown, the conductive layer 11a can be disposed on the entire surface of the silicon-containing particles 11. According to this configuration, the conductivity of the silicon-containing particles 11 is further improved.

[0036] The conductive layer 11a is, for example, a thin film layer containing a conductive material.

[0037] The conductive material can also be a conductive carbon material. That is, the conductive layer 11a can also contain carbon. As a carbon material, natural graphite, artificial graphite, graphitized mesophase carbon, amorphous carbon, soft carbon, and hard carbon can be used. The carbon material can be amorphous carbon. Based on the above, a conductive layer 11a can easily be formed on the surface of the silicon-containing particles 11. Examples of amorphous carbon include carbon black, calcined pitch, coke, and activated carbon.

[0038] Considering the need to ensure conductivity and the diffusion of ions such as Li ions, the thickness of the conductive layer 11a can be greater than 1 nm and less than 200 nm, or greater than 5 nm and less than 100 nm. The thickness of the conductive layer 11a can be measured by scanning electron microscopy (SEM) or transmission electron microscopy (TEM) of the cross-section of the negative electrode active material 20 exposed by the cross-section of the silicon particles 11.

[0039] The following details the composition of the negative electrode active material in Embodiment 1. It should be noted that the following description is applicable to all situations unless otherwise specified. Figure 1 The negative electrode active material 10 shown and Figure 2 The negative electrode active material 20 shown in the modified example are both.

[0040] (Contains silicon particles)

[0041] In this specification, silicon-containing particles 11 refer to particles of a material containing Si. Examples of Si-containing materials include Si, Si alloys, Si compounds, and Si-containing composite materials.

[0042] The silicon-containing particles 11 may be, for example, particles of a composite material containing Si.

[0043] Figure 3 This is a simplified cross-sectional view illustrating an example of a silicon-containing particle 11 being a composite material particle containing Si. In the negative electrode active material 30 of this example, the silicon-containing particle 11 comprises, for example, an ion-conducting phase 14 and a silicon phase 15 dispersed within the ion-conducting phase 14. Hereinafter, the silicon-containing particle 11 having this configuration will be referred to as composite particle 11. The stress caused by the expansion and contraction of the silicon phase 15 during charge and discharge is mitigated by the ion-conducting phase 14, and cracking and breakage of the composite particle 11 are suppressed. Therefore, it is possible to achieve both high capacity and improved charge-discharge cycle characteristics due to the presence of silicon.

[0044] The average particle size of the composite particles 11 can be 1 μm or more and 25 μm or less, or 4 μm or more and 15 μm or less. Based on this configuration, stress caused by volume changes of the composite particles 11 during charging and discharging can be easily mitigated, resulting in good charge-discharge cycle characteristics. Furthermore, by making the surface area of ​​the composite particles 11 appropriately sized, capacity reduction caused by side reactions with the battery electrolyte can be suppressed. It should be noted that even when the silicon-containing particles 11 are not composite particles but rather, for example, Si particles, the average particle size of the silicon-containing particles 11 can be 1 μm or more and 25 μm or less, or 4 μm or more and 15 μm or less.

[0045] The average particle size of composite particles 11 (containing silicon particles 11) refers to the particle size (volume average particle size) that accounts for 50% of the total volume in the particle size distribution determined by laser diffraction scattering. The measuring apparatus can be, for example, the LA-750 manufactured by Horiba, Ltd. (HORIBA).

[0046] Composite particles 11 can be removed from the battery, for example, by the following method. It should be noted that the following method is an example.

[0047] First, the fully discharged battery is disassembled, and the negative electrode is removed. The negative electrode is then cleaned with, for example, anhydrous methyl ethyl carbonate or dimethyl carbonate to remove the anhydrous electrolyte components. The negative electrode compound layer is peeled off from the current collector (e.g., copper foil) serving as the negative electrode core, and the compound layer is pulverized using a mortar to obtain sample powder. Next, the sample powder is dried in a dry atmosphere for 1 hour and then immersed in, for example, gently boiling 6M hydrochloric acid for about 10 minutes to remove elements originating from the composite particles. The sample powder is then washed with deionized water, filtered, and dried at, for example, 200°C for 1 hour. It should be noted that a fully discharged state refers to a depth of discharge (DOD) of 90% or more (state of charge (SOC) of 10% or less).

[0048] The ion-conducting phase 14 may consist of a single phase, or may consist of a plurality of phases.

[0049] The ion-conducting phase 14 contains, for example, at least one selected from the group consisting of a lithium-containing phase and a carbon phase. The lithium-containing phase and the carbon phase have favorable ion conductivity. Therefore, in a case where the ion-conducting phase 14 contains at least one selected from the group consisting of a lithium-containing phase and a carbon phase, absorption and release of ions such as Li ions based on the silicon phase 15 proceed more smoothly via the ion-conducting phase 14. Accordingly, battery characteristics such as initial charge-discharge efficiency and charge-discharge cycle characteristics of the battery can be improved.

[0050] Since the carbon phase has electrical conductivity, even if pores are formed around the composite particle 11, the contact between the composite particle 11 and its surroundings is easily maintained. Accordingly, battery characteristics such as initial charge-discharge efficiency and charge-discharge cycle characteristics of the battery can be improved. The carbon phase may be composed of amorphous carbon (that is, non-crystalline carbon). The amorphous carbon may be hard carbon, soft carbon, or other carbon. Amorphous carbon (non-crystalline carbon) generally refers to a carbon material in which the average interplanar spacing d002 of the (002) plane measured by an X-ray diffraction method exceeds 0.34 nm.

[0051] The lithium-containing phase may contain at least one selected from the group consisting of a lithium aluminate phase and a lithium silicate phase. The lithium aluminate phase and the lithium silicate phase have even more favorable ion conductivity. Therefore, in a case where the ion-conducting phase 14 contains at least one selected from the group consisting of a lithium aluminate phase and a lithium silicate phase, absorption and release of ions such as Li ions based on the silicon phase 15 proceed further smoothly via the ion-conducting phase 14. Accordingly, battery characteristics such as initial charge-discharge efficiency and charge-discharge cycle characteristics of the battery can be improved. In addition, in a case where the ion-conducting phase 14 contains at least one selected from the group consisting of a lithium aluminate phase and a lithium silicate phase, the influence of expansion and contraction of the silicon phase 15 is mitigated by the ion-conducting phase 14.

[0052] Lithium silicate is a silicate containing lithium (Li), silicon (Si), and oxygen (O). The lithium silicate may further contain, for example, elements such as magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), boron (B), and rare earth elements (for example, lanthanum (La)) as other element M1. The atomic ratio O / Si of O to Si in the lithium silicate is, for example, more than 2 and less than 4. In a case where the atomic ratio O / Si is more than 2 and less than 4 (z in the formula described later is 0<z<2), it is advantageous in terms of the stability and lithium ion conductivity of the lithium silicate phase. The atomic ratio O / Si is preferably more than 2 and less than 3. The atomic ratio Li / Si of Li to Si in the lithium silicate is, for example, more than 0 and less than 4. Incidentally, in the present specification, the stability of the lithium aluminate phase includes both chemical stability (alkali resistance) and thermal stability of the lithium aluminate phase.

[0053] The composition of the lithium silicate may be represented by the formula: Li2z SiO 2+z represented by (0<z<2). From the viewpoints of stability, ease of fabrication, lithium ion conductivity and the like, z preferably satisfies the relationship of 0<z<1, and more preferably z=1 / 2. The lithium silicate satisfying z=1 / 2 can be represented by Li2Si2O5.

[0054] Lithium aluminate is an aluminate containing lithium (Li), aluminum (Al) and oxygen (O). The atomic ratio O / Al of O to Al in lithium aluminate is, for example, 1.6 or more and 4 or less. In addition, the atomic ratio Li / Al of Li to Al in lithium aluminate is, for example, 1 / 5 or more and 5 or less. When each of the atomic ratios is within the above ranges, the stability and ionic conductivity of the lithium aluminate phase become more favorable. It should be noted that in the present specification, the stability of the lithium aluminate phase includes both the chemical stability (alkali resistance) and the thermal stability of the lithium aluminate phase.

[0055] In addition to Li, Al and O, the lithium aluminate phase may further contain an element M2. Examples of the element M2 include at least one selected from the group consisting of calcium (Ca), magnesium (Mg), zirconium (Zr), iron (Fe), boron (B), phosphorus (P) and lanthanum (La).

[0056] The element M2 may form a compound. As this compound, depending on the type of the element M2, it may be, for example, an oxide of the element M2, or may be an aluminate of the element M2.

[0057] The element M2 may also be B. That is, the lithium aluminate phase may further contain B. By adding the element M2, for example, the stability and ionic conductivity of the lithium aluminate phase are improved. In addition, by adding the element M2, the porosity of the composite particle 11 can be reduced. As a result, the portions that become starting points of cracks and fractures during repeated charge and discharge are reduced, so that the deterioration of the negative electrode active material is suppressed, and the charge-discharge cycle characteristics of the battery are further improved.

[0058] The lithium aluminate phase may further contain trace amounts of elements such as chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu) and molybdenum (Mo).

[0059] The lithium aluminate phase may be amorphous. At this time, the influence of expansion and contraction of the silicon phase 15 can be alleviated more effectively.

[0060] A highly crystalline, finely crystalline Al2O3 phase can be dispersed within the lithium aluminate phase. The Al2O3 phase, for example, is distributed in an island-like pattern within the lithium aluminate matrix. In this case, the expansion and cracking of the lithium aluminate phase accompanying the expansion and contraction of the silicon phase 15 is easily suppressed, resulting in improved charge-discharge cycle characteristics. In the presence of the Al2O3 phase, a peak originating from the Al2O3 phase can be observed near 2θ = 25.4° in the X-ray diffraction pattern of the composite particles obtained by X-ray diffraction. The Al2O3 content in the composite particles 11 is, for example, 10% by mass or less.

[0061] Silicon phase 15 is the elemental Si phase, which repeatedly absorbs and releases Li ions during battery charging and discharging. Capacity is manifested through the Faraday reaction involving silicon phase 15. Silicon phase 15 has a large capacity. Furthermore, silicon phase 15 expands and contracts significantly during charging and discharging; however, in the negative electrode active material disclosed herein, since silicon phase 15 is dispersed within the ion-conducting phase 14, the stress caused by the expansion and contraction of silicon phase 15 is mitigated by the ion-conducting phase 14.

[0062] The silicon phase 15 can be particulate. For example, the silicon phase 15 is particulate at least before the first charge. The average particle size of the silicon phase 15 can be greater than 1 nm and less than 1000 nm. Alternatively, the average particle size of the silicon phase 15 can be less than 500 nm, less than 200 nm, or less than 50 nm. After the first charge, the average particle size of the silicon phase 15 can be less than 400 nm or less than 100 nm. As described above, by dispersing the fine silicon phase 15 within the ion-conducting phase 14, the volume change of the composite particles during charge and discharge is reduced, and the structural stability of the negative electrode active material is further improved.

[0063] The average particle size of the silicon phase 15 can be determined using SEM images obtained by SEM observation of the cross-section of the negative electrode active material 10, which exposes the silicon phase 15. Specifically, the average particle size of the silicon phase 15 is calculated by averaging the maximum diameters of 100 silicon phase 15 samples randomly selected from the cross-sectional SEM images of the negative electrode active material 10.

[0064] The silicon phase 15 may contain crystalline silicon. The silicon phase 15 may, for example, consist of multiple crystallites. The crystallite size of the silicon phase 15 may be less than 30 nm, less than 20 nm, or less than 15 nm. Based on the above, the volume change caused by the expansion and contraction of the silicon phase 15 during charging and discharging can be reduced, and the improvement in charge-discharge cycle characteristics becomes more significant. The crystallite size of the silicon phase 15 can be calculated based on the half-width of the diffraction peaks originating from the Si(111) plane in the X-ray diffraction pattern obtained by measuring Cu-Kα rays using X-ray diffraction.

[0065] The lower limit of the crystallite size of the silicon phase 15 is not particularly limited, but is 1 nm as an example. A preferred crystallite size for the silicon phase 15 is 1 nm or more and 15 nm or less, or 5 nm or more and 11 nm or less. When the crystallite size of the silicon phase 15 is 1 nm or more, the surface area of ​​the silicon phase 15 can be kept small, thus reducing the likelihood of degradation of the silicon phase 15 associated with irreversible capacity formation. When the crystallite size is 15 nm or less, the expansion and contraction of the silicon phase 15 is more easily homogenized, effectively mitigating stress generated in the negative electrode active material.

[0066] When the ion-conducting phase 14 contains a carbon phase, from the viewpoint of increasing capacity and improving charge-discharge cycle characteristics, the content of the silicon 14 phase in the composite particle 11 can be 30% by mass or more and 80% by mass or less, or 40% by mass or more and 70% by mass or less.

[0067] When the ion-conducting phase 14 contains a lithium silicate phase, from the viewpoint of increasing capacity and improving charge-discharge cycle characteristics, the content of the silicon 14 phase in the composite particle 11 can be 30% by mass or more and 90% by mass or less, or 30% by mass or more and 75% by mass or less.

[0068] When the ion-conducting phase 14 contains a lithium aluminate phase, from the viewpoint of maximizing capacity, the content of the silicon phase 15 in the composite particle 11 can be 30% by mass or more, 35% by mass or more, or 55% by mass or more. From the viewpoint of improving charge-discharge cycle characteristics, the content of the silicon phase 15 in the composite particle can be 95% by mass or less, 75% by mass or less, or 70% by mass or less. In this case, the amount of silicon phase 15 exposed on the surface of the composite particle that is not covered by the lithium aluminate phase is reduced, and the side reactions between the electrolyte and the silicon phase 15 are also suppressed. The content of the silicon phase 15 in the composite particle 11 can be 30% by mass or more and 90% by mass or less, or 35% by mass or more and 75% by mass or less.

[0069] The content of silicon phase 15 in composite particles 11 is determined as described below by quantifying the amount of Si constituting silicon phase 15 in composite particles 11 using Si-NMR.

[0070] The composite particle 11 may further include a conductive layer (not shown) covering at least a portion of the surface of the particle composed of the ion-conducting phase 14 and the silicon phase 15. This conductive layer is equivalent to... Figure 2 The conductive layer 11a shown is composed of particles of ion-conducting phase 14 and silicon phase 15, which are equivalent to the aforementioned parent particles 11b. Based on this configuration, the conductivity of the composite particles 11 is improved.

[0071] (Low-hardness materials)

[0072] As described above, the low-hardness material 13 is at least one selected from the group consisting of minerals with a Mohs hardness of 1 and inorganic compounds with a Mohs hardness of 1. The minerals and inorganic compounds used as the low-hardness material 13 are very soft materials with a Mohs hardness of 1. By attaching such a low-hardness material 13 to the surface of the silicon-containing particles 11, the negative electrode active material of Embodiment 1 can easily move within the negative electrode, and the significant increase in the thickness of the negative electrode due to the expansion of the negative electrode active material during charging can be suppressed.

[0073] Minerals with a Mohs hardness of 1 include, for example, talc. It should be noted that materials referred to by names such as block talc, soapstone, talc powder, and lava can also be used as talc.

[0074] Inorganic compounds with a Mohs hardness of 1 include, for example, molybdenum disulfide.

[0075] The low-hardness material 13 may include at least one selected from the group consisting of talc and molybdenum disulfide. This imparts good sliding properties to the surface of the silicon-containing particles 11, thus enabling more effective reduction of negative electrode expansion.

[0076] The low-hardness material 13 is, for example, granular. The particles of the low-hardness material 13 have a smaller particle size than the silicon-containing particles 11.

[0077] The ratio of the mass of the low-hardness material 13 to the mass of the silicon-containing particles 11 (hereinafter referred to as the "low-hardness material ratio") can be, for example, 0.1% by mass or more and 20% by mass or less, or 0.5% by mass or more and 10% by mass or less. By setting the low-hardness material ratio to 0.1% by mass or more, and ideally 0.5% by mass or more, sufficient sliding properties can be imparted to the surface of the silicon-containing particles 11, thereby further reducing the expansion of the negative electrode. In addition, by setting the low-hardness material ratio to 20% by mass or less, and ideally 10% by mass or less, the increase in resistance of the negative electrode active material caused by the presence of the low-hardness material 13 on the surface of the silicon-containing particles 11 can be reduced, thereby reducing the increase in the internal resistance of the battery. That is, by setting the low-hardness material ratio within the above range, the increase in resistance can be suppressed to a small extent, and the expansion of the negative electrode can be reduced.

[0078] Here, the crystal structure of the low-hardness material can be identified by powder X-ray diffraction, and its elements can be determined and quantified by elemental analysis such as fluorescence X-ray analysis (XRF) and energy-dispersive X-ray spectroscopy (SEM-EDX). In the case of SEM-EDX, it is desirable to set at least 10 particles to be analyzed. When both XRF and SEM-EDX are analyzed using a standard curve with an internal standard method, the results can be obtained more accurately. The content of the element to be analyzed is calculated by averaging the results of the number of analyzed particles and the amount of the element. The mass of the silicon-containing particles 11 and the mass of the low-hardness material 13 are determined from the obtained elemental content. The ratio of the low-hardness material is calculated using the obtained mass of the silicon-containing particles 11 and the mass of the low-hardness material 13.

[0079] (resin)

[0080] As described above, resin 12 is a water-insoluble resin that adheres to at least a portion of the surface of the silicon-containing particles.

[0081] Resin 12 may, for example, comprise at least one selected from the group consisting of styrene-butadiene rubber (SBR), acrylic resins, polyolefin resins, and polyvinylidene fluoride (PVDF). These resins have good adhesive properties, thus enabling the low-hardness material 13 to adhere firmly to the silicon-containing particles 11. Therefore, for example, in preparing the slurry used to form the negative electrode binder layer, even when shear stress is applied to the surface of the negative electrode active material by mixing it with binders and solvents, the low-hardness material 13 can be loaded onto the surface of the silicon-containing particles 11 by means of resin 12. Thus, the negative electrode active material of Embodiment 1 can more reliably reduce the expansion of the negative electrode. To effectively reduce the expansion of the negative electrode, resin 12 may comprise SBR.

[0082] The ratio of the mass of resin 12 to the mass of low-hardness material 13 (hereinafter referred to as the "resin ratio") can be, for example, 0.5% by mass or more and 5% by mass or less. By making the resin ratio 0.5% by mass or more, the low-hardness material 13 can be firmly attached to the silicon-containing particles 11, thus the negative electrode active material 10 can more reliably reduce the expansion of the negative electrode. Furthermore, by making the resin ratio 5% by mass or less, the increase in resistance of the negative electrode active material 10 caused by the presence of resin 12 on the surface of the silicon-containing particles 11 can be reduced, thus reducing the increase in the internal resistance of the battery. In other words, by making the resin ratio within the above range, the increase in resistance can be minimized, and the expansion of the negative electrode can be reduced. To further reduce the increase in resistance, the resin ratio can be 3% by mass or less.

[0083] Here, regarding the resin ratio, the negative electrode active material is first analyzed using time-of-flight secondary ion mass spectrometry (TOF-SIMS), or the resin components are extracted using a resin-soluble solvent (e.g., NMP, GBL, etc.), and quantitative analysis is performed using NMR, GC / MAS, etc., thereby determining the mass of resin 12 in the negative electrode active material 10. The resin ratio is then determined using the mass of the low-hardness material 13 and the mass of the obtained resin 12.

[0084] (Method for manufacturing negative electrode active material)

[0085] The negative electrode active material disclosed herein is manufactured, for example, by a manufacturing method including step I, which obtains silicon-containing particles 11, and step II, which attaches resin 12 and low-hardness material 13 to the surface of silicon-containing particles 11.

[0086] [Process I]

[0087] When the silicon-containing particle 11 is the composite particle 11 described above, the composite particle 11 is manufactured as follows, for example.

[0088] When the ion-conducting phase 14 is a carbon phase, the composite particles 11 are obtained, for example, by pulverizing and micronizing a mixture of a carbon source and raw silicon while stirring in a ball mill or similar device, then heat-treating the mixture in an inactive atmosphere, and finally pulverizing the sinter obtained by the heat treatment. The carbon source may be, for example, sugars such as carboxymethyl cellulose (CMC) or water-soluble resins such as polyvinylpyrrolidone.

[0089] When the ion-conducting phase 14 is a lithium silicate phase, the composite particles 11 can be produced, for example, by the following steps (iA) and (iiA).

[0090] Process (iA) (The process for obtaining lithium silicate)

[0091] Lithium silicate is produced using a raw material mixture containing Si and Li in a specified ratio. Other elements, such as M1, may be included in the raw material mixture as needed. The mixture, containing a specified amount of the above-mentioned raw materials, is dissolved, and the molten liquid is passed through a metal roller to form thin sheets, thus producing lithium silicate. Then, the thinned lithium silicate is crystallized by heat treatment in an atmospheric atmosphere at a temperature above the glass transition temperature and below the melting point. It should be noted that the thinned lithium silicate may also be used without crystallization. Alternatively, lithium silicate may be produced by solid-state reaction through sintering at a temperature below the melting point without dissolving the specified mixture.

[0092] Silicon (Si) raw materials can be silicon dioxide. Li (Li) raw materials can be, for example, lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. They can be used alone or in combination of two or more. Raw materials for element M1 can include oxides, hydroxides, carbonates, hydrides, nitrates, sulfates, etc. Unreacted Si raw materials may remain in lithium silicate. The residual Si raw materials are dispersed as microcrystals of silicon dioxide within the lithium silicate.

[0093] Process (iiA) (The process of obtaining composite particles containing the lithium silicate phase)

[0094] Next, silicon is mixed into lithium silicate to form composite particles. For example, composite particles are produced through the following steps (iiA-a) to (iiA-c).

[0095] Process (iiA-a)

[0096] First, the powdered silicon and the powdered lithium silicate are mixed, for example, at a mass ratio of 20:80 to 95:5. The silicon used should be coarse particles with an average particle size of several μm to tens of μm.

[0097] Process (iiA-b)

[0098] Next, a pulverizing device such as a ball mill is used to simultaneously micronize and pulverize the mixture of raw silicon and lithium silicate, and then compound it. At this stage, an organic solvent can be added to the mixture for wet pulverization. The specified amount of organic solvent can be added to the pulverizing container all at once during the initial stage of pulverization, or it can be added intermittently in multiple stages during the pulverization process. The organic solvent serves to prevent the material being pulverized from adhering to the inner wall of the pulverizing container.

[0099] As organic solvents, alcohols, ethers, fatty acids, alkanes, cycloalkanes, silicates, metal alkoxides, etc. can be used.

[0100] The raw silicon can be coarse particles with an average particle size of several μm to tens of μm. The final silicon particles are preferably controlled such that the crystallite size, calculated by the Scherrer formula from the half-width of the diffraction peaks attributable to the Si(111) plane in the X-ray diffraction pattern, is greater than 5 nm and less than 50 nm.

[0101] It should be noted that silicon and lithium silicate can also be micronized separately and then mixed. Alternatively, silicon nanoparticles and amorphous lithium silicate nanoparticles can be produced without using a pulverizing device, and then mixed together. Known methods such as gas-phase methods (e.g., plasma methods) or liquid-phase methods (e.g., liquid-phase reduction methods) can be used to produce the nanoparticles.

[0102] Process (iiA-c)

[0103] Next, the pulverized material is sintered under pressure, such as by hot pressing, to obtain a sintered body. Sintering is performed, for example, in an inactive atmosphere (e.g., argon, nitrogen, etc.). The sintering temperature is preferably 450°C or higher and 1000°C or lower. Within this temperature range, it is easy to disperse small silicon particles within the low-crystallinity silicate phase. During sintering, lithium silicate softens and flows to fill the gaps between the silicon particles. As a result, a dense, blocky sintered body with a silicate phase as the sea and silicon particles as the islands can be obtained. The sintering temperature is preferably 550°C or higher and 900°C or lower, more preferably 650°C or higher and 850°C or lower. The sintering time is, for example, 1 hour or higher and 10 hours or lower.

[0104] If the obtained sintered body is pulverized, composite particles 11 containing a lithium silicate phase are obtained. By appropriately selecting the pulverization conditions, composite particles 11 with a specified average particle size can be obtained. Through steps (iA) and (iiA), composite particles 11 with a lithium silicate phase as the matrix and a silicon phase dispersed in the matrix are obtained.

[0105] When the ion-conducting phase 14 is a lithium aluminate phase, the composite particles 11 can be produced, for example, by the following steps (iB) and (iiB).

[0106] Process (iB) (The process for obtaining lithium aluminate)

[0107] Lithium aluminate includes, for example, a step of mixing an Al raw material, a Li raw material, and a compound containing element M2 as needed to obtain a mixture; and a step of calcining the mixture to obtain lithium aluminate. Calcination is carried out, for example, in an oxidizing atmosphere. The calcination temperature can be 400°C or higher and 1200°C or lower, or 700°C or higher and 1100°C or lower.

[0108] Examples of Al raw materials include alumina, aluminum hydroxide, and aluminum carbonate. Al raw materials can be used alone or in combination of two or more.

[0109] Examples of lithium feedstocks include lithium carbonate, lithium oxide, lithium hydroxide, and lithium hydride. A single lithium feedstock can be used alone, or two or more can be used in combination.

[0110] The raw materials for element M2 can include oxides, hydroxides, carbonates, hydrides, nitrates, sulfates, etc. of various elements. Element M2 can use one type of raw material alone, or two or more types in combination.

[0111] Lithium aluminate may contain unreacted Al material from the Li production process. When the amount of Al material used relative to Li material is large, Al compounds are more likely to remain. If the residual Al compound in lithium aluminate is Al₂O₃, it is possible that an Al₂O₃ phase dispersed within the lithium aluminate phase will form in the final composite particles.

[0112] Process (iiB) (Process for obtaining composite particles containing lithium aluminate phase)

[0113] Next, silicon is mixed into lithium aluminate to form composite particles. For example, composite particles are produced through the following steps (iiB-a) to (iiB-c).

[0114] Process (iiB-a)

[0115] First, the raw silicon powder and lithium aluminate powder are mixed at a mass ratio of, for example, 20:80 to 95:5. The raw silicon can be coarse particles with an average particle size of several μm to tens of μm.

[0116] Process (iiB-b)

[0117] Next, a pulverizing device such as a ball mill is used to simultaneously micronize and pulverize the mixture of raw silicon and lithium aluminate, and then compound it. At this stage, an organic solvent can be added to the mixture for wet pulverization. The specified amount of organic solvent can be added to the pulverizing container all at once during the initial stage of pulverization, or it can be added intermittently in multiple stages during the pulverization process. The organic solvent serves to prevent the material being pulverized from adhering to the inner wall of the pulverizing container.

[0118] As organic solvents, alcohols, ethers, fatty acids, alkanes, cycloalkanes, silicates, metal alkoxides, etc. can be used.

[0119] The raw silicon can be coarse particles with an average particle size of several μm to tens of μm. The final silicon particles are preferably controlled such that the crystallite size, calculated by the Scherrer formula from the half-width of the diffraction peaks attributable to the Si(111) plane in the X-ray diffraction pattern, is greater than 5 nm and less than 50 nm.

[0120] It should be noted that silicon and lithium aluminate can also be micronized separately and then mixed. Alternatively, silicon nanoparticles and amorphous lithium silicate nanoparticles can be prepared without using a pulverizing device and then mixed. Known methods such as gas-phase methods (e.g., plasma methods) or liquid-phase methods (e.g., liquid-phase reduction methods) can be used to prepare the nanoparticles.

[0121] Process (iiB-c)

[0122] Next, the pulverized material is sintered under pressure, such as by hot pressing, to obtain a sintered body. Sintering is performed, for example, in an inactive atmosphere (e.g., argon, nitrogen, etc.). The sintering temperature is preferably 450°C or higher and 1000°C or lower. Within this temperature range, it is easy to disperse small silicon particles within the low-crystallinity silicate phase. During sintering, lithium aluminate softens and flows to fill the gaps between the silicon particles. As a result, a dense, blocky sintered body with lithium aluminate phase as the sea and silicon particles as the islands can be obtained. The sintering temperature is preferably 550°C or higher and 950°C or lower, more preferably 650°C or higher and 900°C or lower. The sintering time is, for example, 1 hour or higher and 10 hours or lower.

[0123] If the obtained sintered body is pulverized, composite particles 11 containing the lithium aluminate phase are obtained. By appropriately selecting the pulverization conditions, composite particles 11 with a specified average particle size can be obtained. Through steps (iB) and (iiB), composite particles 11 with the lithium aluminate phase as the matrix and a silicon phase dispersed in the matrix are obtained.

[0124] When the composite particle 11 has the aforementioned conductive layer, the conductive material constituting this conductive layer is preferably a conductive carbon material, as described above. Examples of methods for covering the surface of the parent particle with carbon material include: CVD methods using hydrocarbon gases such as acetylene or methane as raw materials; and methods involving mixing and heating the parent particle with coal tar pitch, petroleum tar pitch, phenolic resin, etc., to carbonize it. Alternatively, carbon black can be deposited onto the surface of the parent particle. For example, a conductive layer can be formed on the surface of the parent particle by heating a mixture of the parent particle and carbon material in an inactive atmosphere (e.g., argon, nitrogen, etc.) at a temperature of 700°C or higher and 950°C or lower. As described above, a conductive layer is obtained... Figure 2 The composite particle 11 shown has a conductive layer 11a on the surface of the parent particle 11b.

[0125] It should be noted that, as step I for obtaining silicon-containing particles 11, the method for producing composite particles 11 as silicon-containing particles 11 has been described above, but commercially available silicon-containing particles such as Si particles can also be prepared as silicon-containing particles 11.

[0126] [Process II]

[0127] Step II is the process of attaching resin 12 and low-hardness material 13 to the surface of silicon-containing particles 11.

[0128] There are no particular limitations on the method by which the resin 12 and the low-hardness material 13 are adhered to the surface of the silicon-containing particles 11. As an example, the following method can be used.

[0129] First, a slurry containing resin 12 and low-hardness material 13 is prepared. For example, when using SBR as resin 12 and talc as low-hardness material 13, the slurry can be prepared by mixing SBR latex with talc. The mass ratio of resin 12 to low-hardness material 13 in the slurry can be determined by considering the mass ratio of resin 12 to low-hardness material 13 in the target negative electrode active material.

[0130] The aforementioned slurry is added to the silicon-containing particles 11, such as the composite particles 11 obtained in step I, and mixed. While mixing, the mixture is slowly dried to obtain a mixture in a near-powder state. Then, the mixture is dried to obtain a powder. Thus, a low-hardness material 13 is obtained, in which a powder adheres to the surface of the silicon-containing particles 11 by means of resin 12. This powder can be used as the negative electrode active material of Embodiment 1.

[0131] (Implementation Method 2)

[0132] The negative electrode of Embodiment 2 includes a negative electrode binder layer containing an active material. The active material includes the negative electrode active material of Embodiment 1. As described in Embodiment 1, the negative electrode active material of Embodiment 1 can reduce the expansion of the negative electrode due to charging. Therefore, the negative electrode of Embodiment 2 can reduce the expansion caused by charging.

[0133] Figure 4 This is a simplified cross-sectional view showing an example of the negative electrode configuration in Embodiment 2. (e.g.) Figure 4 As shown, the negative electrode 40 of Embodiment 2 includes, for example, a negative electrode mixture layer 41 and a negative electrode current collector 42. The negative electrode mixture layer 41 is disposed on the negative electrode current collector 42 and contains the negative electrode active material of Embodiment 1.

[0134] In addition to the negative electrode active material of Embodiment 1, the negative electrode compound layer 41 may also contain other negative electrode active materials such as carbon materials. By including carbon materials as the negative electrode active material, even when the negative electrode active material of Embodiment 1 expands and contracts during charge and discharge, the conductive path in the negative electrode active material can be ensured, thus further suppressing capacity degradation during charge and discharge cycles. Furthermore, by including carbon materials, the porosity in the negative electrode compound layer 41 becomes easier to control, thus allowing for porosity control while also considering electrolyte permeability. The carbon material that functions as the negative electrode active material is, for example, at least one selected from the group consisting of graphite, soft carbon, and hard carbon.

[0135] The negative electrode binder layer 41 may also include, for example, a binder. Examples of binders include fluorinated resins such as PVDF, polyacrylonitrile (PAN), polyimide, acrylic resins, polyolefins, SBR, etc. Alternatively, these resins may be used in combination with carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts, polyvinyl alcohol (PVA), etc.

[0136] The binder may contain SBR and PAA. In this case, the ratio of the total mass of SBR and PAA to the mass of the active material contained in the negative electrode binder layer 41 may be, for example, 3% by mass or more and 10% by mass or less. Therefore, the negative electrode 40 of Embodiment 2 can further reduce expansion due to charging.

[0137] To reduce the resistance of the negative electrode 40, the negative electrode compound layer 41 may also contain a conductive additive. Examples of conductive additives include carbon materials and conductive polymer compounds. Examples of carbon materials include carbon black, graphite, acetylene black, carbon nanotubes, carbon nanofibers, graphene, fullerene, and graphite oxide. Examples of conductive polymer compounds include polyaniline, polypyrrole, and polythiophene.

[0138] The negative current collector 42 can be a sheet or film made of metallic materials such as stainless steel, nickel, copper, or their alloys. The sheet or film can be porous or non-porous. Metal foil, metal mesh, etc., can be used as the sheet or film. Carbon materials such as carbon can be coated onto the surface of the negative current collector 42 as a conductive auxiliary material.

[0139] (Implementation Method 3)

[0140] The battery in Embodiment 3 includes a positive electrode, a negative electrode, and an electrolyte. The negative electrode is the same as that in Embodiment 2. Based on this configuration, the battery in Embodiment 3 can reduce the expansion of the negative electrode due to charging.

[0141] Figure 5 This is a schematic longitudinal sectional view illustrating an example of the battery according to Embodiment 3. The battery 100 is a cylindrical battery comprising a cylindrical battery casing, a wound electrode assembly 54, and an electrolyte (not shown). The electrode assembly 54 is housed within the battery casing and is in contact with the electrolyte.

[0142] The battery casing consists of a bottomed cylindrical metal container, namely the casing body 55, and a sealing body 56 that seals the opening of the casing body 55. A gasket 67 is disposed between the casing body 55 and the sealing body 56. The gasket 67 ensures the airtightness of the battery casing. Inside the casing body 55, insulating plates 57 and 58 are respectively disposed at both ends of the electrode assembly 54 in the winding axis direction of the electrode assembly 54.

[0143] The housing body 55, for example, has a stepped portion 61. The stepped portion 61 is formed by partially stamping the side wall of the housing body 55 from the outside. The stepped portion 61 may also be formed in an annular shape along the circumference of an imaginary circle defined by the housing body 55 on the side wall of the housing body 55. In this case, the sealing body 56 is supported, for example, by the surface on the opening side of the stepped portion 61.

[0144] The sealing body 56 includes a partially open metal plate 62, a lower valve body 63, an insulating member 64, an upper valve body 65, and a cover 66. These components are stacked in this order within the sealing body 56. The sealing body 56 is installed at the opening of the housing body 55 such that the cover 66 is located outside the housing body 55, and the partially open metal plate 62 is located inside the housing body 55.

[0145] The components constituting the sealing body 56 are, for example, circular or ring-shaped. All of these components, except for the insulating component 64, are electrically connected to each other.

[0146] The electrode assembly 54 has a positive electrode 51, a separator 52, and a negative electrode 53. The positive electrode 51, separator 52, and negative electrode 53 are all strip-shaped. The width direction of the strip-shaped positive electrode 51 and negative electrode 53 is, for example, parallel to the winding axis of the electrode assembly 54. The separator 52 is disposed between the positive electrode 51 and the negative electrode 53. The positive electrode 51 and negative electrode 53 are wound into a spiral shape with the separator 52 spaced between them.

[0147] When observing the cross-section of the battery 100 in a direction perpendicular to the winding axis of the electrode assembly 54, the positive electrode 51 and the negative electrode 53 are alternately stacked in the radial direction of an imaginary circle defined by the housing body 55, with spacers 52 between them.

[0148] The positive electrode 51 is electrically connected to the cover 66, which also serves as the positive terminal, via a positive electrode lead 59. One end of the positive electrode lead 59 is connected, for example, near the center of the positive electrode 51 along its length. The positive electrode lead 59 extends from the positive electrode 51 to the partially open metal plate 62 through a through hole formed in the insulating plate 57. The other end of the positive electrode lead 59 is, for example, soldered to the side of the electrode assembly 54 of the partially open metal plate 62.

[0149] The negative electrode 53 is electrically connected to the housing body 55, which also serves as the negative terminal, via a negative electrode lead 60. One end of the negative electrode lead 60 is connected, for example, to the end of the negative electrode 53 along its length. The other end of the negative electrode lead 60 is, for example, soldered to the inner bottom surface of the housing body 55.

[0150] The following is a detailed explanation of the components of battery 100.

[0151] The positive electrode 51 comprises a material having the property of absorbing and releasing metal ions (e.g., lithium ions). The positive electrode 51 may, for example, comprise a positive electrode active material. The positive electrode 51 may, for example, have a positive electrode current collector and a positive electrode flux layer loaded on the surface of the positive electrode current collector.

[0152] As a positive current collector, a sheet or film made of metallic materials such as aluminum, stainless steel, titanium, and their alloys can be used. Aluminum and its alloys are inexpensive and easy to fabricate into thin films, making them suitable materials for positive current collectors. The sheet or film can be porous or non-porous. Metal foils, metal meshes, etc., can be used as sheets or films. Carbon materials such as carbon can be coated on the surface of the positive current collector as conductive auxiliary materials.

[0153] The positive electrode layer contains the positive electrode active material. This active material can be a material capable of absorbing and releasing metal ions (e.g., lithium ions). Examples of suitable positive electrode active materials include lithium-containing transition metal oxides, lithium-containing transition metal phosphates, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal oxysulfides, and transition metal oxynitrides. In particular, using lithium-containing transition metal oxides or lithium-containing transition metal phosphates as the positive electrode active material can reduce battery manufacturing costs and increase the average discharge voltage. Examples of lithium-containing transition metal oxides include lithium cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, and lithium nickel manganese oxide. Examples of lithium-containing transition metal phosphates include lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, and lithium nickel phosphate.

[0154] The positive electrode binder layer may also include a binder. The material described in Embodiment 2 as a binder that can be used in the negative electrode binder layer may also be used in the positive electrode binder layer.

[0155] The positive electrode mixture layer may also include a conductive additive. As a conductive additive, the material described in Embodiment 2 as a conductive additive that can be used in the negative electrode mixture layer may also be used in the positive electrode mixture layer.

[0156] The negative electrode 53 is the negative electrode 40 of embodiment 2.

[0157] The electrolyte used as the electrolyte may contain a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The concentration of the lithium salt in the electrolyte may, for example, be 0.5 mol / L or more and 2 mol / L or less. By controlling the lithium salt concentration within the above range, an electrolyte with excellent ionic conductivity and moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.

[0158] As a non-aqueous solvent, cyclic carbonates, linear carbonates, cyclic ethers, linear ethers, nitriles, amides, etc., can be used. One of these solvents can be used, or two or more can be used in combination.

[0159] As lithium salts, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bisperfluoroethylsulfonylimide (LiN(SO2C2F5)2), LiAsF6, LiCF3SO3, and lithium difluoro(oxalate-containing)borate, etc., can be used. One of these electrolyte salts can be used, or two or more can be used in combination.

[0160] Typically, a separator is desired between the positive and negative electrodes. The separator 52 has high ion permeability and possesses moderate mechanical strength and insulation. Microporous membranes, woven fabrics, and nonwoven fabrics can be used as the separator 52. The material used for the separator 52 can be, for example, a polymer. The polymer can be, for example, polyolefins such as polypropylene and polyethylene.

[0161] In the battery of Embodiment 3, the electrolyte may, for example, be impregnated in a polymer that serves as a separator. That is, the battery of Embodiment 3 may have a structure that combines an electrolyte and a polymer.

[0162] The battery of Embodiment 3 may further include a solid electrolyte as the electrolyte. That is, the battery of this disclosure may have a hybrid structure that combines an electrolyte and a solid electrolyte. Examples of solid electrolyte materials are halide solid electrolytes, sulfide solid electrolytes, oxide solid electrolytes, or organic polymer solid electrolytes. In this disclosure, "halide solid electrolyte" refers to a solid electrolyte containing a halogen element as the main component of the anions. "Sulfide solid electrolyte" refers to a solid electrolyte containing sulfur as the main component of the anions. "Oxide solid electrolyte" refers to a solid electrolyte containing oxygen as the main component of the anions. The main component of the anions refers to the anion with the largest molar mass among all the anions constituting the solid electrolyte.

[0163] As an example of the structure of the battery in Embodiment 3, it is explained Figure 5 The illustrated configuration example shows a cylindrical non-aqueous electrolyte secondary battery consisting of a wound electrode assembly with the positive and negative electrodes separated by a separator and an electrolyte housed in an outer packaging. However, the battery disclosed herein is not limited to this configuration example. The battery of Embodiment 3 can be any shape, such as square, coin-shaped, button-shaped, or laminated. Furthermore, instead of the wound electrode assembly, other types of electrode assemblies, such as those formed by stacking the positive and negative electrodes separated by a separator, can be used in the battery of Embodiment 3.

[0164] (Other implementation methods)

[0165] (Postscript)

[0166] Based on the description of the above embodiments, the following technology is disclosed.

[0167] (Technology 1)

[0168] A negative electrode active material, which possesses:

[0169] Silicon-containing particles;

[0170] At least a portion of the water-insoluble resin adhering to the surface of the silicon-containing particles; and

[0171] The low-hardness material adheres to the surface of the silicon-containing particles using the resin.

[0172] The low-hardness material is at least one selected from the group consisting of minerals with a Mohs hardness of 1 and inorganic compounds with a Mohs hardness of 1.

[0173] This configuration reduces the expansion of the negative electrode caused by charging.

[0174] (Technology 2)

[0175] According to the negative electrode active material of technique 1, the silicon-containing particles have a conductive layer on at least a portion of the surface.

[0176] This structure can improve the conductivity of silicon-containing particles.

[0177] (Technology 3)

[0178] According to the negative electrode active material of technique 1 or 2, the low-hardness material comprises at least one selected from the group consisting of talc and molybdenum disulfide.

[0179] Based on this configuration, the expansion of the negative electrode caused by charging can be further reduced more effectively.

[0180] (Technology 4)

[0181] According to any one of the following technical methods, the ratio of the mass of the low-hardness material to the mass of the silicon-containing particles is 0.5% by mass or more and 10% by mass or less.

[0182] Based on this configuration, the expansion of the negative electrode due to charging can be further reduced.

[0183] (Technology 5)

[0184] The negative electrode active material according to any one of techniques 1 to 4, wherein the resin comprises at least one selected from the group consisting of styrene-butadiene rubber, acrylic resins, polyolefin resins and polyvinylidene fluoride.

[0185] Based on this configuration, the expansion of the negative electrode due to charging can be further and reliably reduced.

[0186] (Technology 6)

[0187] According to any one of techniques 1 to 5, the negative electrode active material wherein the mass ratio of the resin to the mass of the low-hardness material is 0.5% by mass or more and 5% by mass or less.

[0188] Based on this configuration, the increase in resistance can be minimized, and the expansion of the negative electrode can be reduced.

[0189] (Technology 7)

[0190] A negative electrode having a negative electrode mixture layer containing active material.

[0191] The active material comprises any one of the negative electrode active materials described in techniques 1 to 6.

[0192] With this configuration, the negative electrode of technology 7 can reduce expansion caused by charging.

[0193] (Technology 8)

[0194] According to the negative electrode of technology 7, the negative electrode mixture layer further comprises a binder.

[0195] The adhesive comprises styrene-butadiene rubber and polyacrylic acid.

[0196] The ratio of the total mass of the styrene-butadiene rubber and the polyacrylic acid to the mass of the active substance is more than 3% by mass and less than 10% by mass.

[0197] Based on this configuration, it is possible to further reduce expansion caused by charging.

[0198] (Technology 9)

[0199] A battery that has the following features:

[0200] A negative electrode comprising the negative electrode active material described in technique 7 or 8;

[0201] Positive electrode; and

[0202] Electrolytes.

[0203] According to this configuration, the battery of technology 9 can reduce the expansion of the negative electrode caused by charging.

[0204] Example

[0205] The present disclosure will now be described in more detail using examples. These examples are merely illustrative and are not intended to limit the scope of the disclosure.

[0206] <Preparation of Negative Electrode Active Material>

[0207] [Examples 1-13]

[0208] (Preparation of composite particles)

[0209] Lithium carbonate (Li₂CO₃) as a Li raw material and silicon dioxide (SiO₂) as a Si raw material were mixed at an atomic ratio of Si / Li of 1.05 to obtain a mixture. The mixture was calcined at 800°C for 10 hours in an inert gas atmosphere to obtain lithium silicate (Li₂Si₂O₅). The obtained lithium silicate was pulverized to an average particle size of 10 μm.

[0210] The pulverized lithium silicate was mixed with raw silicon (3N, average particle size 10 μm) at a mass ratio of 40:60. The mixture was then filled into a jar (SUS, volume: 500 mL) of a planetary ball mill (Fritsch P-5). Next, 24 SUS balls (20 mm in diameter) were placed in the jar, the lid was closed, and the mixture was pulverized at 200 rpm for 50 hours in an inactive atmosphere.

[0211] Next, the powdered mixture was taken out in an inactive atmosphere and sintered at 600°C for 4 hours under pressure based on a hot press in the same inactive atmosphere to obtain a sintered body of the mixture. The sintered body of the mixture was pulverized and passed through a 40 μm sieve to obtain composite particles (composite particles containing silicate phase). Then, using a sieve, composite particles with an average particle size of 10 μm were obtained.

[0212] The silicon phase has a crystallite size of 15 nm. The silicon phase is granular with an average particle size of 20 nm. The main component of the silicate phase is Li₂Si₂O₅, and the silicon phase accounts for 60% by mass of the composite particles containing the silicate phase.

[0213] (Preparation of negative electrode active material)

[0214] SBR latex (manufactured by ENEOS Material Co., Ltd., TRD105A) and talc (manufactured by Talc Co., Ltd., Nanoace D-1000) were mixed in a ratio of SBR mass to talc mass (resin ratio) as shown in Table 1 to prepare a slurry. This slurry was then added to the composite particles prepared by the above method in a ratio of talc mass to composite particle mass (low-hardness material ratio) as shown in Table 1, and mixed. While mixing in a mortar, the mixture was slowly dried to obtain a near-powder state. The mixture was then dried to obtain a powder. This powder was used as the negative electrode active material.

[0215] (Making the negative electrode)

[0216] Graphite and the negative electrode active material obtained by the above method were mixed at a mass ratio of graphite:negative electrode active material = 7:3 to obtain a mixture. This mixture was used as the active material for the negative electrode (hereinafter referred to as the negative electrode active material mixture). As a binder, a mixed binder of SBR (manufactured by ENEOS Material Co., Ltd., TRD 105A), PAA (manufactured by Toa Synthetic Co., Ltd.), and CMC (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., CELLOGEN BSH-6) was used. The negative electrode active material mixture was mixed with the binder, and water was further added as a dispersion medium to prepare the negative electrode slurry. The total mass ratio of SBR and PAA relative to the negative electrode active material mixture is shown in Table 1. In addition, CMC was added at a mass percentage of 1% relative to the negative electrode active material mixture. The mass ratios of SBR and PAA relative to the negative electrode active material mixture are shown in Table 2. Next, the negative electrode slurry was coated on both sides of the copper foil, which serves as the negative electrode current collector, and after the coating was dried, it was calendered. Cut to the specified size, and fabricate a negative electrode with a negative electrode binder layer formed on both sides of the negative electrode current collector. At this time, a portion of the negative electrode current collector is provided to expose the negative electrode current collector.

[0217] (The production of the positive electrode)

[0218] A suitable amount of N-methyl-2-pyrrolidone (NMP) was added to a positive electrode mixture prepared by mixing positive electrode active material, acetylene black, and PVDF in a mass ratio of positive electrode active material:acetylene black:PVDF = 95:2.5:2.5, followed by stirring to prepare a positive electrode slurry. The positive electrode active material used was LiNi... 0.88 Co 0.09 Al 0.03 O2 represents a lithium transition metal composite oxide. Next, a positive electrode paste is coated on both sides of an aluminum foil serving as the positive electrode current collector. After the coating is dried, it is calendered. It is then cut to a specified size to form a positive electrode with a positive electrode paste layer formed on both sides of the positive electrode current collector. At this time, a portion of the positive electrode current collector is exposed.

[0219] (Preparation of non-aqueous electrolytes)

[0220] A non-aqueous electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1.2 mol / L in a mixed solvent consisting of ethylene carbonate (EC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of EC:FEC:EMC:DMC = 10:10:5:75.

[0221] (Fabrication of a non-aqueous electrolyte secondary battery)

[0222] An aluminum positive electrode lead is installed on the exposed portion of the positive current collector of the positive electrode, and a nickel negative electrode lead is installed on the exposed portion of the negative current collector of the negative electrode. The positive and negative electrodes are wound into a spiral shape with a polyolefin separator in between, and then the electrode body is housed in an outer packaging body made of aluminum laminate. After injecting a non-aqueous electrolyte, the opening of the outer packaging body is sealed to obtain the battery.

[0223] [Comparative Example 1]

[0224] In the fabrication of the negative electrode, the composite particles prepared in Examples 1-13 were directly used as the negative electrode active material. That is, talc was not attached to the surface of the composite particles, and they were used as the negative electrode active material. Otherwise, the negative electrode was fabricated using the same method as in Examples 1-13.

[0225] The fabrication of the positive electrode, the preparation of the non-aqueous electrolyte, and the fabrication of the non-aqueous electrolyte secondary battery are the same as in Examples 1-13.

[0226] [Comparative Example 2]

[0227] In the preparation of the negative electrode active material, silica with a Mohs hardness of 7 was used instead of talc. Otherwise, the negative electrode active material was prepared using the same method as in Examples 1-13.

[0228] The fabrication of the negative electrode, the positive electrode, the preparation of the non-aqueous electrolyte, and the fabrication of the non-aqueous electrolyte secondary battery are the same as in Examples 1-13.

[0229] [Comparative Example 3]

[0230] In the fabrication of the negative electrode, the composite particles prepared in Examples 1-13 were directly used as the negative electrode active material. That is, talc was not attached to the surface of the composite particles, and they were used as the negative electrode active material. In addition, talc was added to the negative electrode mixture slurry. As shown in Table 1, the proportion of talc added to the negative electrode mixture slurry was 1% by mass relative to the negative electrode active material mixture.

[0231] The fabrication of the positive electrode, the preparation of the non-aqueous electrolyte, and the fabrication of the non-aqueous electrolyte secondary battery are the same as in Examples 1-13.

[0232] <Battery Review>

[0233] For the batteries of Examples 1-13 and Comparative Examples 1-3, the expansion rate of the negative electrode and the internal resistance of the battery were evaluated by the following methods.

[0234] (Determination of the expansion rate of the negative electrode during charging)

[0235] For the negative electrode of each embodiment and comparative example, the rate of expansion during charging was determined. A battery was fabricated using the fabricated negative electrode, and the rate of expansion during charging of the negative electrode was determined using the battery by the following method.

[0236] (1) Use the prepared negative electrode, and use the positive electrode and electrolyte to make a battery.

[0237] (2) Charge the battery at 0.1C at 25°C until the battery voltage reaches 4.2V, then discharge it at 0.1C until the battery voltage reaches 2.5V. Calculate the thickness (Ta) of the negative electrode in the fully charged state. It should be noted that the thickness (Ta) of the negative electrode in the fully charged state is determined by disassembling the battery, removing the negative electrode, and measuring its thickness.

[0238] (3) The negative electrode thickness (Tb) before charging is determined by measuring the negative electrode thickness during battery manufacturing.

[0239] (4) Calculate the thickness increase rate (Ta×100 / Tb-100) of the negative electrode in the charging state relative to the thickness of the negative electrode before charging, and use it as the expansion rate (%) of the negative electrode during charging.

[0240] Here, the thickness of the negative electrode is measured using a digital micrometer manufactured by NiKON Corporation. Specifically, the thickness is measured at any 5 locations, and the average value calculated from the 5 measurements is taken as the thickness.

[0241] The results are shown in Table 1. It should be noted that the values ​​shown in Table 1 are relative to the negative electrode expansion rate of Comparative Example 1 (100%).

[0242] (Measurement of internal resistance)

[0243] The internal resistance of the batteries in each embodiment and comparative example was measured. Initial charge and discharge were performed under the following conditions.

[0244] Initial charge and discharge conditions

[0245] Charge the battery at a constant current of 0.1It (30mA) until the battery voltage reaches 4.2V. Then, discharge the battery at a constant current of 0.1It (30mA) until the battery voltage reaches 2.5V.

[0246] Next, under the following conditions, charging and discharging were performed, and the initial DC internal resistance (DCIR) was investigated using the following equation (a). The results are shown in Table 1.

[0247] • Charge and discharge conditions

[0248] At a temperature of 25°C, the system was charged with a constant current of 0.3It (90mA) until the state of charge (SOC) reached 50%. After a 2-hour pause, the system was discharged for 10 seconds with a current of 0.5It (150mA).

[0249] DCIR calculation formula

[0250] DCIR(mΩ) = (Voltage before discharge begins - Voltage 10 seconds after discharge begins) / (Discharge current density × Electrode area) … (a)

[0251] The results are shown in Table 1. It should be noted that the values ​​shown in Table 1 are relative to the DCIR value of Comparative Example 1 (100%).

[0252] [Table 1]

[0253]

[0254] [Table 2]

[0255]

[0256] (Inspection)

[0257] As shown in Table 1, in the negative electrodes of Examples 1-13, which used negative electrode active materials in which a low-hardness material (talc) was attached to the surface of silicon-containing particles using resin (here, SBR), the expansion rate was lower than that of the negative electrode active material of Comparative Example 1, which used negative electrode active materials in which no low-hardness material was attached to the surface of silicon-containing particles. That is, the negative electrode active material of this disclosure can reduce the expansion of the negative electrode during charging. Furthermore, the internal resistance of the batteries using the negative electrode active materials of Examples 1-13 was the same as that of the negative electrode active material of Comparative Example 1, which did not have the low-hardness material, so there was no problem with an increase in internal resistance.

[0258] In Comparative Example 2, where silica with a Mohs hardness of 7 is attached to the surface of silicon-containing particles, a reduction in negative electrode swelling during charging could not be confirmed. Furthermore, in Comparative Example 3, where talc is mixed into the negative electrode mixture instead of being attached to the surface of silicon-containing particles, a reduction in negative electrode swelling during charging could not be confirmed. These results confirm that negative electrode active materials with a low hardness of 1 (Mohs hardness of 1) attached to the surface of silicon-containing particles via resin can reduce negative electrode swelling.

[0259] In the above embodiments, talc was used as a low-hardness material. However, the inventors have also confirmed that the expansion of the negative electrode can be reduced when using a low-hardness material (such as molybdenum disulfide) with the same Mohs hardness as talc.

[0260] Industrial availability

[0261] The technology disclosed herein is useful for batteries such as lithium-ion secondary batteries.

Claims

1. A negative electrode active material, which possesses: Silicon-containing particles; At least a portion of the water-insoluble resin adhering to the surface of the silicon-containing particles; and The low-hardness material adheres to the surface of the silicon-containing particles using the resin. The low-hardness material is at least one selected from the group consisting of minerals with a Mohs hardness of 1 and inorganic compounds with a Mohs hardness of 1.

2. The negative electrode active material according to claim 1, wherein, The silicon-containing particles have a conductive layer on at least a portion of the surface.

3. The negative electrode active material according to claim 1, wherein, The low-hardness material comprises at least one selected from the group consisting of talc and molybdenum disulfide.

4. The negative electrode active material according to claim 1, wherein, The ratio of the mass of the low-hardness material to the mass of the silicon-containing particles is more than 0.5% by mass and less than 10% by mass.

5. The negative electrode active material according to claim 1, wherein, The resin comprises at least one selected from the group consisting of styrene-butadiene rubber, acrylic resins, polyolefin resins, and polyvinylidene fluoride.

6. The negative electrode active material according to claim 1, wherein, The ratio of the mass of the resin to the mass of the low-hardness material is 0.5% by mass or more and 5% by mass or less.

7. A negative electrode having a negative electrode mixture layer comprising an active substance, The active material comprises the negative electrode active material according to any one of claims 1 to 6.

8. The negative electrode according to claim 7, wherein, The negative electrode mixture layer also includes a binder. The adhesive comprises styrene-butadiene rubber and polyacrylic acid. The ratio of the total mass of the styrene-butadiene rubber and the polyacrylic acid to the mass of the active substance is more than 3% by mass and less than 10% by mass.

9. A battery comprising: The negative electrode as described in claim 7; Positive electrode; and Electrolytes.

Citation Information

Patent Citations

  • Non-aqueous secondary cell functional layer composition, non-aqueous secondary cell member, and non-aqueous secondary cell

    WO2019194194A1